Subplate Neurons as an Organizer of Mammalian Neocortical Development - Ohtaka-Maruyama, Chiaki (Frontiers in Neuroanatomy, 2020)
Subplate neurons (SpNs) are a transient cell population that play an important role in the early development of the neocortex. They are one of the earliest born and matured neurons in the developing cerebral cortex. It is known that they play an essential role in thalamo-cortical axon pathfinding and the establishment of the first neural circuit from the thalamus towards cortical layer IV. In addition to this function, it has recently been revealed that SpNs play an important role in the regulation of radial neuronal migration during the mid-embryonic stage. As SpNs are unique to mammals, they may have contributed to the evolution of the mammalian neocortex by efficiently organizing cortical formation during the limited embryonic period of corticogenesis. By increasing our knowledge of the functions of SpNs, we will clarify how SpNs act as an organizer of mammalian neocortical formation.